Alternative Inactivated Poliovirus Vaccines Adjuvanted with Quillaja brasiliensis or Quil-A Saponins Are Equally Effective in Inducing Specific Immune Responses - de Costa, Fernanda; Yendo, Anna Carolina A.; Cibulski, Samuel P.; Fleck, Juliane D.; Roehe, Paulo M.; Spilki, Fernando R.; Gosmann, Grace; Fett-Neto, Arthur G. (PLOS ONE, 2014)
Inactivated polio vaccines (IPV) have an important role at the final stages of poliomyelitis eradication programs, reducing the risks associated with the use of attenuated polio vaccine (OPV). An affordable option to enhance vaccine immunogenicity and reduce costs of IPV may be the use of an effective and renewable adjuvant. In the present study, the adjuvant activity of aqueous extract (AE) and saponin fraction QB-90 from Quillaja brasiliensis using poliovirus antigen as model were analyzed and compared to a preparation adjuvanted with Quil-A, a well-known saponin-based commercial adjuvant. Experimental vaccines were prepared with viral antigen plus saline (control), Quil-A (50 µg), AE (400 µg) or QB-90 (50 µg). Sera from inoculated mice were collected at days 0, 28, 42 and 56 post-inoculation of the first dose of vaccine. Serum levels of specific IgG, IgG1 and IgG2a were significantly enhanced by AE, QB-90 and Quil-A compared to control group on day 56. The magnitude of enhancement was statistically equivalent for QB-90 and Quil-A. The cellular response was evaluated through DTH and analysis of IFN-γ and IL-2 mRNA levels using in vitro reestimulated splenocytes. Results indicated that AE and QB-90 were capable of stimulating the generation of Th1 cells against the administered antigen to the same extent as Quil-A. Mucosal immune response was enhanced by the vaccine adjuvanted with QB-90 as demonstrated by increases of specific IgA titers in bile, feces and vaginal washings, yielding comparable or higher titers than Quil-A. The results obtained indicate that saponins from Q. brasiliensis are potent adjuvants of specific cellular and humoral immune responses and represent a viable option to Quil-A.